A Discrete Mechanics Approach to the Cosserat Rod Theory — Part II: Geometric Insights About Static Equilibria on Vertex and Staggered Grids - Lang, Holger; Sato Martin de Almagro, Rodrigo; Wang, Tengman; Stavole, Martina; Linn, Joachim; Leyendecker, Sigrid (International Journal for Numerical Methods in Engineering, 2025)
We apply the discrete mechanics approach to the discretisation of geometrically exact Cosserat rods. We consider discrete Cosserat rods defined on a vertex (or nodal) grid, as well as on a staggered grid, and provide a review and update of the results already obtained in Part I for the nodal model variant and, for the first time, present a detailed version for the staggered variant. Several numerical examples underline the validity of the presented theory.<br